2020
DOI: 10.1111/acer.14494
|View full text |Cite
|
Sign up to set email alerts
|

Does the Combination Matter? Examining the Influence of Alcohol and Cannabis Product Combinations on Simultaneous Use and Consequences in Daily Life

Abstract: Background Alcohol and marijuana/cannabis are frequently used simultaneously (i.e., SAM use). SAM use is complex, and the ways in which alcohol and cannabis are simultaneously used may reveal differential effects. The purpose of this study was to examine day‐level effects of distinct alcohol and cannabis product combinations on simultaneous use and consequences on that day. Methods College student SAM users (N = 274; 50% women; Mage = 19.82 years) were recruited to complete 54 days of data collection, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2122
2122

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 74 publications
0
14
0
1
Order By: Relevance
“…For instance, the use of high-potency products, such as cannabis concentrates, was associated with more alcohol consequences on co-use days among college students who use both alcohol and cannabis. 114 This finding has been replicated in another study based on online surveys of respondents who reported co-use of alcohol and cannabis; respondents were categorized by high- versus low-THC product use. Those categorized as using high-THC products reported drinking more on cannabis use days relative to those who used low-THC products.…”
Section: Resultsmentioning
confidence: 79%
“…For instance, the use of high-potency products, such as cannabis concentrates, was associated with more alcohol consequences on co-use days among college students who use both alcohol and cannabis. 114 This finding has been replicated in another study based on online surveys of respondents who reported co-use of alcohol and cannabis; respondents were categorized by high- versus low-THC product use. Those categorized as using high-THC products reported drinking more on cannabis use days relative to those who used low-THC products.…”
Section: Resultsmentioning
confidence: 79%
“…It is yet unknown whether the shift away from liquor will maintain once students return to campuses. If so, this may represent a positive change, given risks (e.g., blackouts) associated with rapidly rising blood alcohol concentrations that can occur upon taking “shots” (Labrie et al, 2011; Mochrie et al, 2019; Newman and Abramson, 1942) and as liquor, compared to beer or wine, consumption leads to experiencing more negative consequences (Stevens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, lifetime diagnosis of alcohol dependence has been found to increase the risk for lifetime cannabis dependence ( 43 ). On the other hand, although alcohol and marijuana/cannabis are frequently used simultaneously, studies suggest that acute negative consequences of co-use are associated with using more than one alcohol product ( 44 ).…”
Section: Discussionmentioning
confidence: 99%